When sustainability speaks louder: the role of ESG in mitigating the impact of manager personality traits on earnings management in credit cooperatives - Renata Pesente; Kachirí Vitória Noara Farias; Cristian Baú Dal Magro; Larissa de Lima Trindade; Mauricio Leite (Revista Ambiente Contábil, 2025)
Purpose: To analyze the moderating effect of ESG practices on the relationship between manager personality traits and earnings management practices in credit cooperatives.